Walkerton: Lessons learned in comparison with waterborne outbreaks in the developed world. Issue 6 (1st November 2002) - Hrudey, S E; Huck, P M; Payment, P; Gillham, R W; Hrudey, E J
Abstract : An estimated 2300 people became seriously ill and 7 died from exposure to microbially contaminated drinking water in the town of Walkerton, Ontario, in May of 2000. The severity of this drinking water disaster resulted in the Government of Ontario calling a public inquiry by Mr. Justice Dennis O'Connor to address the cause of the outbreak, the role, if any, of government policies in contributing to this outbreak, and ultimately, the implications of this experience on the safety of drinking water across the province of Ontario. This paper summarizes relevant evidence presented at the inquiry by the expert panel together with Justice O'Connor's findings addressing the circumstances of the outbreak. These findings are reviewed in relation to the published causes of previous waterborne disease outbreaks that have been reported elsewhere in developed countries. The circumstances surrounding the Walkerton tragedy are an important source of knowledge for those concerned with providing safe drinking water to the public. Although some circumstances are obviously specific to this epidemic, others echo common themes in waterborne outbreaks that have occurred before. These common themes suggest the need for attention to broad issues of drinking water safety in addition to the individual specific details that often command attention. Key words : waterborne disease, Escherichia coli O157:H7, Campylobacter jejuni, Cryptosporidium, Giardia, multiple barriers, health risk.